2012
DOI: 10.1111/j.1439-0531.2012.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Characterization of Porcine IZUMO1, an IgSF Family Member

Abstract: IZUMO1, belonging to the family of mammalian immunoglobulin proteins, has been well characterized in the mouse. Here, we describe the molecular cloning and expression analysis of porcine IZUMO1 (pIZUMO1). Partial sequence information published in the National Center for Biotechnology Information (NCBI) database was used to generate the full-length sequence for IZUMO1 using rapid amplification of cDNA ends (RACE). A search of the porcine genomic sequence in the NCBI database identified a bacterial artificial ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In the pig IZUMO1 still forms complexes; however, these are mainly homodimers of IZUMO1 (Kim et al 2013). As seen in the work by Ellerman et al (2009) complexes of this size are most likely formed by interactions between the extracellular portion of the protein, therefore it is unsurprising that pig IZUMO1 forms complexes of this size, even without a long cytoplasmic region.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the pig IZUMO1 still forms complexes; however, these are mainly homodimers of IZUMO1 (Kim et al 2013). As seen in the work by Ellerman et al (2009) complexes of this size are most likely formed by interactions between the extracellular portion of the protein, therefore it is unsurprising that pig IZUMO1 forms complexes of this size, even without a long cytoplasmic region.…”
Section: Discussionmentioning
confidence: 90%
“…55 aa), shorter in humans (approx. 40 aa) and very short in porcine species -only one amino acid in length (an alanine) (Kim et al 2013). In order to investigate the importance of this region, this study produced a mutated mouse line with a truncated version of IZUMO1.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we showed that bIZUMO1 is expressed on the surface of sperm as a homodimeric complex. Inter-IZUMO1 complex formation was recently described during mouse IZUMO1 immunoprecipitation experiments, and it was suggested that the protein forms a homodimeric complex in mouse sperm [ 13 , 14 ]. Indeed, most immunoglobulin superfamily members have been reported to exert their function in various biological processes, such as germ cell migration, transmigration of leucocytes and viral invasion, through homophilic and heterophilic interactions [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al . () subsequently cloned and characterized the porcine IZUMO1 gene, raised an anti‐porcine IZUMO1 antibody, and analyzed the expression of IZUMO1 in porcine species. Furthermore, they found that IZUMO1 is well conserved across species (pig, crab‐eating macaque, mouse and bull).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of IZUMO has also been analyzed in porcine species, and shown to be specific to boar sperm (Kim et al . ). In humans, the relationship between IZUMO and infertility has been studied, and anti‐IZUMO antibodies have been found in serum samples from immunoinfertile women (Clark & Naz ).…”
Section: Introductionmentioning
confidence: 97%